Armadillo (2020)
The Armadillo Roller 1 is a product that answer to need to move in a city with a transportation system as complex as Bogotá, where there is already different solutions, but this don't answer to how the city is built. The Roller 1 is a product design for young people and adults that seek for a new way to move around the city, this product has been though carefully around how it could move around the city without any worries about the ground or weather, feeling comfortable to ride and having easy access to it. In the other hand, its unique style as an scooter with a wooden deck and a carbon fiber body made it easy to recognize differentiating from all the other products, but when its not in use it camouflage in all the other personal objects of the user.